POTENTIAL PHARMACOLOGICAL ACTIVITIES OF FALOAK BARK (STERCULIA QUADRIFIDA R. BR) AS AN HERBAL PLANT FROM EAST NUSA TENGGARA: A SCOPING REVIEW - Fuadah, Shofiatul; Istikharah, Rochmy; Tenda, Priska Ernestina; Ramadani, Arba Pramundita (Universitas Muhammadiyah Magelang, 2025)
Faloak bark (Sterculia quadrifida R. Br) is part of the faloak plant, which has been used for a long time in traditional medicine to treat a variety of medical conditions. Faloak bark is claimed to possess medicinal properties that can treat liver, kidney, and bladder diseases, cure gastroenteritis, hepatitis, anemia, malaria, back pain, and function as an energy booster. Recent studies in pharmacology have found that faloak bark has several interesting biological properties, thus strengthening its potential as a new source of active ingredients for pharmaceutical development. This study literature aims to provide a concise overview of the evaluations of the secondary metabolite chemicals found in faloak bark, thus highlighting their potential pharmacological properties. To find articles for the review of the pharmacological activities of faloak bark, a search was conducted on research journal databases using Publish or Perish 8, and 43 papers relevant to the evaluation were found. Literature review showed that faloak bark contains many different chemicals, such as alkaloids, gallic acid derivatives, flavonoids, polyphenols, saponins, steroids, tannins, terpenoids, triterpenoids, quinone, glycoside, as well as isolates of 2,3-dihydro-6-hydroxy-2-methylenenaphtho[1,2-b] furan-4,5-dione, and 2-iminoethyl 2-(1-hydroxypentan-2-yl) phenyl) acetate. Faloak bark has such pharmacological properties as antiaging, antibacterial, antibiofilm, anti-dengue, antifungal, anti-hepatitis C, anti-hyperglycemia, anticancer, antimalarial, antioxidant, antipyretic, and immunomodulatory effects. Therefore, faloak bark has considerable potential for the advancement of herbal remedies.